The effect of ethical leadership on work engagement and workaholism: Examining self-efficacy as a moderator - Widdy Muhammad Sabar Wibawa; Yoshi Takahashi (Administrative Sciences, 2021)
This study aims to investigate how ethical leadership can influence work engagement and workaholism through the potential moderating effect of self-efficacy. There have been debates on the similarities, their negative correlation, and differences between these two work outcomes. To show one new aspect of evidence regarding the debate, we chose ethical leadership as the common antecedent of the outcomes and analyzed the relationships while considering a boundary condition, self-efficacy. For this purpose, using an online questionnaire, we collected primary data from 80 graduate students from a university in Indonesia. An experimental research design was applied, and we used t-test and hierarchical regression analysis to confirm the relationship mentioned above. Results indicate that ethical leadership has a positive effect on work engagement, while it has an insignificant effect on workaholism. Moreover, self-efficacy did not moderate the relationships between ethical leadership and work engagement, or ethical leadership and workaholism. One novelty of the present study is the finding of different consequences of the two 'similar' work outcomes from ethical leadership. Implications, limitations, and direction for future research are also discussed.
Keywords: 350; ethical leadership; experimental research design; personal resource; self-efficacy; work engagement; workaholism